The UK Seasonal Worker Visa. Issue 3 (September 2022) - Mantouvalou, Virginia
Abstract: This article discusses the United Kingdom (UK) 2019 Seasonal Worker Visa, which was adopted to address labour shortages in horticulture. It explains the challenges faced by workers in agriculture more broadly, and the particular issues raised by seasonal visas. It argues that the UK scheme contains significant restrictions on workers' rights. The article situates this scheme in a framework of 'state-mediated structures of injustice', namely instances where legal rules with an appearance of legitimacy create or increase vulnerability and are connected to widespread structures of exploitation. This theoretical framework focuses on the role and responsibility of the state for workers' exploitation. The authorities have political responsibility to change these rules, and may also have legal responsibility to do so under human rights law.